Video: The New Rules of Communication - Christian Mossner; Dennis Herhausen (Marketing Review St.Gallen, 2017)
Although video communication offers the potential to engage with employees and consumers, many established firms adopt video as a new communication medium quite slowly and with little enthusiasm. Based on our experience with leading national and international firms, we introduce a four step approach to help companies in adopting a video communication strategy, summarize the main obstacles that firms typically face, and provide recommendations on how to overcome these obstacles.
Keywords: 650